A clustering‐based review on project portfolio optimization methods. (5th January 2021) - Saiz, Miguel; Lostumbo, Marisa A.; Juan, Angel A.; Lopez‐Lopez, David
Abstract: Project portfolio management and optimization constitutes a critical activity for organizations in different industrial sectors and business. The scientific literature in this subject is extremely vast, which makes it difficult to understand the connections among the existing approaches and perspectives. This paper provides a clustering map of the existing work on the subject, thus identifying the main trends and approaches from different scientific communities. After analyzing each of the identified clusters, the paper provides insights and emerging trends that can be useful both for researchers and practitioners in the area.